Development of Rossi: Enhancing English Reading Skills by Using the Literacy Wheel Media - Oktadela, Resy; Shalawati, Shalawati; Hadiyanti, Putri Octa; Elida, Yusti; Nurrahmi, Nurrahmi (Journal of English Language and Education, 2024)
This research stems from the low reading proficiency observed among students during the the process of teaching English learning, which impacted various sectors, including primary education. The issue was especially prominent in English, a mandatory subject that needs to be mastered from an early age. Consequently, efforts were made to support students in learning English through the development of an interactive educational tool called "Roda Literasi" (Rossi), designed to enhance students' learning motivation. This study focuses on evaluating the validity and practicality of the developed learning media. The research involved third-grade students from SD IT Imam Syafei’I and followed a Research and Development (RD) approach using the ADDIE model. Data collection included preliminary interviews, validation by subject matter and media experts, and feedback from teachers and students through questionnaires. Results indicated that "Roda Literasi" aligned with 95% of the subject matter and achieved a 98% validity score for educational use. Additionally, 88.93% of students reported enjoying the use of the tool. Based on these findings, the researcher recommends expanding the content of Roda Literasi to include other subjects.